Mengendus Pengalaman Puncak Keagamaan - Frederikus Fios (Bina Nusantara University, 2011)
Religion is one exclusive vocabulary in religious. This institution arranges the relationship of religious with God, Devine Substance that was being prayed in mondial religions. Religious, including spiritualists, that accommodated in one religion must have altogether consciousness in an altogether identity that signed their devotional practices, rites, and spiritual practices that they actualized in togetherness circumstances (communal). Religion and spiritualism are elements having special-unique function for groups of people to internalize. A basic question that keeps claiming role and function of religion today that it is challenged to disclose factual experience that could significantly contribute for better quality in social life from time to time. Moreover, actual issue that writer will discuss is discourse related to religious summit experience topic in believe dynamic. It is included in explaining multidimensional aspect that shows religious experience being applied to fix human quality life into positive and also to fulfill hopes of people.